(untitled) (Journal of Comparative Social Work, 2024)
It is an intrinsic feature of many public agencies that they are dependent on street-level bureaucrats making important decisions regarding their clients. While some have claimed that such decisions are in danger of being corrupted by the bureaucrats’ discretionary powers, Lipsky argued that this discretion was necessary for the proper implication of social policy. However, the digitalization of government has altered the way in which many public servants reach their decisions. For instance, Bovens and Zouridis have argued that digitalization limits or removes bureaucrats’ processional discretion when making decisions, which can have a negative effect on public services. While decisions are singular events, the process of reaching them is complex and drawn out over time. Therefore, the purpose of this article is to explore the process of decision-making in a public service context, and how digitalization has impacted caseworker discretion. The context of this study is the Norwegian child welfare service, where we have conducted focus group interviews with 26 caseworkers. Our analyses of the decision-making process uncovered several points in which digitalization has increased the need for caseworker discretion, i.e., an increased availability of caseworkers, information gathering and the admissibility of private information online. Our study demonstrates how even though digital technology such as social media presents new opportunities for information gathering, it also poses a danger for the creation of discriminatory practices toward citizens that could negatively affect the quality of service provision. Furthermore, conceptually deconstructing the decision-making process was beneficial to understanding how digitalization impacts different aspects of the case-handling process.